(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Modern broadcasting and a number of special radio transmitters have an output power of the order of tens and hundreds of kilowatts. Any improvement aimed at increasing the efficiency can provide significant economic benefits. The task of improving the energy efficiency in modern transmitters should be solved taking into account the requirements of the standards for the value of nonlinear distortion and for the level of out-of-band emissions. The issue of device reliability is also important. Until recently, PWM transmitters have had the best efficiency. Pulse width modulation is used in almost all medium wave transmitters. The disadvantages of this method of generating the output signal include the need to use powerful vacuum devices in the output stage of such transmitters. This does not allow using the advantages of modern semiconductor element base. In transistor transmitters with an output power of more than several hundred watts, the amplifiers of the final stage are built according to the block-modular principle. In a typical design of such devices, the powers of individual transistor amplifier modules operating in class B are added together. In addition to the advantages due to the use of a semiconductor element base, such transmitters have better reliability compared to tube transmitters. Failure of one or part of the amplifier modules will lead to deterioration in the characteristics of the transmitter, but will not lead to a complete loss of performance.